PENERAPAN MODEL LEARNING CYCLE 5E UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA SMP NEGERI 6 BALFAI KUPANG TENGAH TAHUN AJARAN 2019/2020 - Zipora Anita Tode; Fransina Th. Nomleni; Jusuf Blegur (Prodi Pendidikan Biologi FKIP Universitas Kristen Artha Wacana, 2021)
ABSTRACT Based on a statement by the science class VIIA middle school teacher n 6 middle school Balfai mussels, on classification material teachers have not applied a devoted modal of learning only monoton pafa teacher. This invoves having students become passive ( recording and being less creative in optimizing all of the skills in them for the laerning process that results in low learning. Thestudent”s ability to remember, understand, apply, analyze,edit anf produce anything from the materis is stiil less becausw students are srill glaued to books and talks and lack of practices given by the teacher. Unquote student VIIA class of this materieal from a total of 25 students is only 10 pople who meet the minumum criteia for ketchness. One attempt to address the promblem is to implement a learning model in order to improve the results of the student cocktail cycle . The kind of research thats structured in research is a class action study, the instrument used i our research is obserform and test, data analysis used for descriptions and percents. Keywords : The Learning Cycle 5e Model To Increase The Cognitive Results Of Students